Phyllodes tumor of the breast. Clinical case - Mariya N. Lun'kova; Elena V. Litvyakova; S.A. Ivanov; A.D. Kaprin; Marina V. Kiseleva (LLC "MEDIAFORMAT", 2024)
Rare breast neoplasms are found by physicians in clinical practice. Phyllodes tumor of the breast accounting for 0.3-1% of all breast neoplasms is one of these neoplasms. Today, the phyllodes tumor etiology is unclear, the same as its pathogenesis. The paper reports an example of successful surgical treatment of malignant phyllodes tumor.